Implementasi Kebijakan Pemerintah Dalam Merelokasi Pedagang Kaki Lima Di New Mall Pasar Sentral Kota Makassar - Adityawan, Muh Afif; Madani, Muhlis; Parawangi, Anwar (Universitas Muhammadiyah Makassar, 2021)
The purpose of this study was to find out how to implement the Government in Relocating Street Vendors and the factors that supported and inhibited the Implementation of Government Policy in Relocating Street Vendors (PKL) at the New Mall Sentral Market Makassar City. This research used descriptive qualitative and qualitative methods. The number of informants in this study were 4 people. The results of the study stated that the Implementation of Government Policy in Relocating Street Vendors in the Sentral Market of Makassar City was carried out by: communicating the relationship through discussion, meetings and socialization; increasing resources in the form of increasing the number of staff, do posposition in the form of management assistance and security of traders who wanted to be relocated: and facilitated the bureaucratic structure to be more effective in handling relocation. Supporting factor in the Implementation of Government Policy in Relocating Street Vendors (PKL) in New Market Pasar Makassar City Mall, consisted of: internal factors, in the form of the sellers who wanted to be relocated to a more comfortable place and not burdensome in terms of contributions.Keywords: Policy implementation, Relocation, Street Vendors (PKL)